2000
DOI: 10.1063/1.126698
|View full text |Cite
|
Sign up to set email alerts
|

Strain relief via trench formation in Ge/Si(100) islands

Abstract: Trenches formed at Ge/Si(100) island bases become an effective strain-relief mechanism at high growth temperatures. Trenches result from diffusion of the most highly strained material to regions of lower strain. The trench depth self-limits, scaling linearly with island diameter. A simple atomistic model of island elasticity indicates that this self-limiting behavior is of kinetic rather than energetic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 13 publications
9
59
2
Order By: Relevance
“…5͑c͒. This apparent breakdown of the model predictions is not surprising; mature domes are well known to dig deep trenches around their periphery, 12 inducing island enrichment with Si, and therefore influencing the relative stability of islands vs WL. As already pointed out, our model does not consider the role played by SiGe alloying and cannot be directly used to infer the system behavior when intermixing is important.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…5͑c͒. This apparent breakdown of the model predictions is not surprising; mature domes are well known to dig deep trenches around their periphery, 12 inducing island enrichment with Si, and therefore influencing the relative stability of islands vs WL. As already pointed out, our model does not consider the role played by SiGe alloying and cannot be directly used to infer the system behavior when intermixing is important.…”
Section: Modelingmentioning
confidence: 99%
“…The tendency toward higher island aspect ratios is counterbalanced by competing effects. It is well known that temperature-dependent SiGe alloying takes place in the islands and deep trench formation occurs 12 around steep islands providing a simple kinetic path for Si spill out from the substrate. Since alloying lowers the effective misfit between island and substrate, this process decreases the volumetric term, thus allowing shallow islands to be stable even at larger volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Already in 1999, Chaparro et al 14 pointed out that ͕105͖ hut clusters grown at T Ն 550°C contained non-negligible amounts of Si. In a further seminal paper the authors showed 15 that Si becomes available when deep enough trenches ͑drilling the Ge wetting layer and reaching the Si underneath͒ form around the island perimeter to relieve the strong compression present around the island base. 16,17 In more recent times, SiGe distributions within islands of various shape have been investigated with great detail, exploiting refined x-ray measurements and/or selective etching techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the Si/Ge system it is known that atoms diffuse away from the highest strain regions and create trenches. 16 In dislocation-induced ordering like that in this work and in Ge/Si quantum dots 14 the alignment observed is difficult to explain by the strain field from dislocations, since the dislocation core is far from the dot nucleation sites and the strain field of dislocations decreases abruptly with distance from their core. 17 Here alignment could be a result of preferential nucleation on the shear steps that form on the surface.…”
Section: Resultsmentioning
confidence: 90%